2021
DOI: 10.3892/ol.2021.12693
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GPER by E2 promotes proliferation, invasion and migration of breast cancer cells by regulating the miR‑124/CD151 pathway

Abstract: Breast cancer is one of the most common malignancies worldwide and is responsible for a high mortality rate. However, the underlying pathological mechanism of breast cancer remains unclear. MicroRNAs (miRNAs/miRs) play critical roles in the progression of breast cancer. Recent studies have reported that miR-124/CD151 participates in the development of breast cancer. However, the exact molecular mechanism of miR-124/CD151 action in 17β-estradiol (E2)-treated breast cancer cells remains unknown. Thus, the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
(56 reference statements)
0
10
1
Order By: Relevance
“…Particularly, GPER activation by E2 and/or specific ligand of GPER, G1 [75], determines multiple intracellular events such as EGFR transactivation leading to rapid ERK1/2 activation, PLC and PI3K phosphorylation, AC stimulation, and intracellular calcium mobilization [37,69,[76][77][78] involved in cell proliferation and apoptosis modulation [38][39][40]79]. GPER involvement in breast [80,81], endometrial [82], and ovarian [83] cancer progression has been reported. However, studies demonstrated that it can mediate anti-proliferative effects also in BC [79], PC [84], and OC [85] and can induce apoptosis in LCT [38] and ACC [40] cell lines.…”
Section: Duality Of Estrogen Receptors Function In Cancermentioning
confidence: 99%
“…Particularly, GPER activation by E2 and/or specific ligand of GPER, G1 [75], determines multiple intracellular events such as EGFR transactivation leading to rapid ERK1/2 activation, PLC and PI3K phosphorylation, AC stimulation, and intracellular calcium mobilization [37,69,[76][77][78] involved in cell proliferation and apoptosis modulation [38][39][40]79]. GPER involvement in breast [80,81], endometrial [82], and ovarian [83] cancer progression has been reported. However, studies demonstrated that it can mediate anti-proliferative effects also in BC [79], PC [84], and OC [85] and can induce apoptosis in LCT [38] and ACC [40] cell lines.…”
Section: Duality Of Estrogen Receptors Function In Cancermentioning
confidence: 99%
“…The additional layer of the regulation of E2 genomic action is the interaction of ERs with various coactivators (CoA), such as transcription factor Sp1 (SP1), which modulate the binding of activated E2-ER complex with ERS [ 136 ]. Non-genomic action of E2 via binding to GPER1 leads to signal transduction through the G protein, which results in the synthesis of cAMP [ 137 , 138 , 139 ] and activation of downstream signaling pathways: phosphatidylinositol 3-kinase (PI3K), Akt kinase, Ca 2+ signaling, and MAP kinases [ 140 ]. In breast tumors, estrogenic activation of GPER1 leads to the induction of proliferation, migration, or angiogenesis [ 141 , 142 ].…”
Section: Micrornas (Mirnas) In Breast Cancermentioning
confidence: 99%
“…Results presented by Yang H. and co-workers are important examples of cross-talk between miRNAs and ER signaling, as in their study, E2 decreased the expression of miR-124, while increasing GPER1 expression in MCF-7 cells. GPER-E2 signaling suppressed miR-124 and led to overexpression of CD151, and in addition, promoted proliferation, invasion, and migration of breast cancer cells [ 137 ]. This interplay between ERα, GPER1, and miRNAs is an important element of resistance to anti-estrogen therapy since it has been demonstrated that antagonists of the Erα, such as tamoxifen or fulvestrant, may activate GPER1 [ 164 ].…”
Section: Micrornas (Mirnas) In Breast Cancermentioning
confidence: 99%
“…In addition, GPER activation has been observed to play a critical role in breast cancer growth, proliferation, migration, and metastasis [ 76 ] via the modulation of different molecular pathways. These include the stabilization of the F-actin cytoskeleton and the upregulation of Yes-Associated Protein 1 (YAP) and Transcriptional coactivator with a PDZ-binding domain (TAZ) via the activation of Gαq-11, Phospholipase C beta (PLCβ)/PKC and Rho/Rho-associated protein kinase (ROCK) signaling [ 87 , 88 ]; the downregulation of microRNA-124 (miR124) and miR-148a to promote proliferation and support immune invasion via the upregulation of CD151, HOX Transcript Antisense RNA (HOTAIR) and Histocompatibility Antigen, class I, G (HLA-G) [ 89 , 90 , 91 ]; the enhancement of Fibronectin (FN) matrix assembly and anchorage-independent growth [ 92 ]; and cell survival through the activation of epidermal growth factor receptor (EGFR)/ERK/c-Fos/Activator Protein 1 (AP-1) for Sirtuin 1 (SIRT1, also known as NAD-dependent deacetylase sirtuin-1) upregulation [ 93 ], MAPK/ERK/Tripartite Motif Containing 2 (TRIM-2) for Bcl-2-like protein 11 (BIM) downregulation [ 94 ], and EGFR/PI3K for Forkhead Box O3s (FOXO3a) inhibition [ 95 ]. Moreover, GPER appears to be required for stemness maintenance in cancer stem cells via PKA/Bcl-2 associated agonist of cell death (BAD) pathway [ 96 ] and the development of chemoresistance via EGFR/ERK/Akt-mediated ATP Binding Cassette, Subfamily G, Member 2 (ABCG2) expression [ 97 ].…”
Section: Membrane Steroid Receptors and Their Role In Hormone-sensitive Cancersmentioning
confidence: 99%